Implementasi Myoware Sensor Otot untuk Alat Bantu Terapi Penderita Drop hand dan Pasca Stroke - Rahmatul yoga Setiawan; Anton Anton; Tuti Anggraini (Elektron : Jurnal Ilmiah, 2022)
The manufacture of therapeutic aids for patients with drop hand and post-stroke controlled by a microcontroller has been carried out. The objectives of this study are (a) applying muscle sensor myoware to make therapeutic aids for patients with hand drop and post-stroke controlled by a microcontroller and (b) measuring the performance of the device. The research method starts from making tools, and measuring tool performance. The results of measuring the performance of the tool are shown by the myoware muscle sensor readings, when the muscle contracts the voltage is 4.8V and the ADC is 984. The sensor accuracy level is MAX30100 for 99% oxygen readings based on the sensor measurement results compared to a medical pulse oximeter. The measurement results are displayed on the OLED LCD. Overall the tool can function well. Suggestions for further research, can be added data communication based on Internet of Things and machine learning for training motion methods.